Political Economy of Institutions, Democracy and Voting - Schofield, Norman; Caballero, Gonzalo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book presents the latest research  in the field of Political Economy, dealing with the integration of economics and politics and the way institutions affect social decisions. The authors are eminent scholars from the U.S., Canada, Britain, Spain, Italy, Mexico and the Philippines. Many of them have been influenced by Nobel laureate Douglass North, who pioneered the new institutional social sciences, or by William H. Riker who contributed to the field of positive political theory. The book focuses on topics such as: case studies in institutional analysis; research on war and the formation of states; the analysis of corruption; new techniques for analyzing elections, involving game theory and empirical methods; comparing elections under plurality and proportional rule, and in developed and new democracies.  .
Introduction -- Institutions: Rules or Equilibria? -- War, Wealth, and the Formation of States -- Why Do Weak States Prefer Prohibition to Taxation? -- Self-enforcing, Public-order Institutions for Contract Enforcement: Litigation, Regulation, and Limited Government in Venice, 1050 - 1350 -- Judicial Stability During Regime Change: Apex Courts in India 1937-1960 -- Institutional Arrangements Matter for Both Efficiency and Distribution: Contributions and Challenges of the New Institutional Economics -- Institutional Foundations, Committee System and Amateur Legislators in the Governance of the Spanish Congress: An Institutional Comparative Perspective (USA, Argentina, Spain) -- Coalition Governments and Electoral Behavior: Who Is Accountable? -- Democracy and Voting: Empirical and Formal Models of the United States Presidential Elections in 2000 and 2004 -- Modelling Elections in Post-Communist Regimes: Voter Perceptions, Political Leaders and Activists -- Electoral Systems and Party Responsiveness -- Electoral Institutions and Political Corruption: Ballot Structure, Electoral Formula, and Graft -- A Model of Party Entry in Parliamentary Systems with Proportional Representation -- Moving in Time: Legislative Party Switching as Time-Contingent Choice -- On the Distribution of Particularistic Goods -- Vote Revelation: Empirical Content of Scoring Rules.
Keywords: Political science; Public finance; Economic theory; Political Science; Public Economics; Economic Theory/Quantitative Economics/Mathematical Methods